Mussels enhance digestive enzyme activity in preparation for stressful fluctuating environments - Jordan A. James Bond; Petra I. Escobar; Newton Z. Hood; Helen C. Hong; Daniel R. Rankins; Grace Chan; Jade V. Betancourt; Karina Brocco French; Nichole D. Procter; Beck A. Wehrle; Kwasi M. Connor (Journal of Comparative Physiology B, 2026)
Elevated heat and low phytoplankton abundance are physiologically and ecologically challenging marine organisms of the northeast Pacific, including the mussel Mytilus californianus . During low tide, mussels are exposed to warm air and undergo anaerobic metabolism. Tidal variation coincides with daily fluctuations in food availability requiring flexible response systems (e.g., changes in digestive enzyme activity) to maintain homeostasis. In this study we allowed mussels to acclimate in tidal mesocosms with or without aerial heat across high and low levels of food abundance, after which we measured amylase (carbohydrase) activity and gene expression. Remarkably, enzyme activity was unpredictably elevated during low tide in fasted or moderate heat-stress (+ 8 °C; 23 °C) conditions, thereby potentially mitigating energy losses posed by environmental stress. Heat stress combined with fasting (multistressor) presented a marked challenge for mussels as evidenced by lower amylase activity compared to other treatments. A subsequent acute aerial heat-shock (+ 17 °C; 32 °C) negatively impacted amylase activity across all acclimation groups. Gene expression of amylase was anticorrelated with activity suggestive that mussels’ sense environmental fluctuations and respond by regulating digestive enzyme activity. Although mussels can employ these strategies to dampen short-term stress, the heatwaves predicted to persist in their ecosystems in the future may curtail their effectiveness.